Children are everywhere : conspicuous reproduction and childlessness in reunified Berlin - Joshi, Meghana (Fertility, reproduction, and sexuality, 2024)
"Children are Everywhere engages with how demographic anxieties and reproductive regimes emerge as forms of social inclusion and exclusion in a low fertility Western European context. This book explores everyday experiences of parenting and childlessness of 'ethnic' Germans in Berlin, who came of age around the fall of the Berlin Wall, and brings them into conversation with theories on parenting, waithood, non-biological intimacies, and masculinities. This is the first ethnographic work by a South Asian author on demographic anxieties and reproduction in Germany and reverses the anthropological gaze to study Europe as the 'Other.'"--